Knowledge Sharing in the 3D Agora-world - Jensen, Sisse Siggaard (Proceedings of the International Conference on Networked Learning, 2004)
This paper will first introduce a theoretical grounding for understanding knowledge sharing in avatar-based sessions in a 3D world. Secondly, it will present observations from 12 explorative sessions undertaken while building and exploring social interaction with avatars in a 3D Agora world. These observations are summarized in three scenarios: “Voyage of discovery”, “Playful meeting” and “Purposeful meeting” and in a conclusion suggesting a “reflective design” approach. Research has been carried out in a special interest group (Agora SIG 5) on “Knowledge sharing across knowledge cultures” in the EU project EQUEL.